Assimilating Indonesia Chinese Muslim in Makassar (1967-1997) - Nurhayati Nurhayati (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2018)
The ethnic Chinese Muslims in Makassar has been there since the year 1606 in conjunction with Islam in Makassar. Dato ri Bandang was the one who initiated the spread of Islam among Chinese people of Makassar. During the new order, ethnic Chinese Muslims in Makassar city had done the intermingling with local communities. The new order had kept many discriminatory elements contains policy against ethnic Chinese in the city of Makassar. This is the sort of policy that directly affects the life of the field of social, cultural, political and religious. Although they are more successful in the field of economics. Even so, ethnic Chinese Muslims in Makassar when it is capable of performing a merging in all areas of social life.